Information literacy module based on Schoolwide Enrichment Model (SEM) - Mohamed Shuhidan, Shamila; Baharuddin, Mohammad Fazli; Jaffar, Kamaruzaman; Jaafar, Hazlina (Universiti Teknologi MARA, Kedah, 2017)
Learning in the 21st century requires students a new way of thinking, knowledge, skills and abilities to manage the information and in preparation to face the challenges of the competitive world ahead. Students are encouraged to have the information skills as the ability to access and evaluate information to help make effective selection and resolution. However studies have found issues in students’ competence, environmental instability, security, trust, and privacy using the Internet for information searching in their learning environment. Due to that, Information Literacy Module based on Schoolwide Enrichment Model has been developed. Information Literacy Module based on Schoolwide Enrichment Model is a guideline or reference used by Teacher-Librarian at Maktab Rendah Sains MARA (MRSM) for the purpose of guiding students to seek information on the success of scientific studies or social science studies through the Schoolwide Enrichment Model (SEM) program. This initiative was the collaboration of experts from the Faculty of Information Management, UiTM and the Teacher-Librarians from MRSM which are particularly involved in the implementation of the SEM program. As an expert and facilitator in information science discipline, Teacher-Librarian should enhance their information skills to be productive and proactive in helping students, classroom teachers and staff in identify accurate and relevant information in various formats of information especially in digital era. The SEM model basically focuses on the development of intelligent capabilities and behaviors within the learning and education area to students. This model is very different from the learning model ever implemented in Malaysia as students are given the opportunity to enhance their creativity and to face the various challenges that need to be solved. This makes the cognitive power of these students progress. This model will help them when in university later.